Experiment of oxygenated fuel on diesel engine: Properties, performance and emission - Hazman, Abu Hassan; R., Mamat; Hagos, F. Y.; Gholamhassan, Najafi (2019)
Diesel engines have been found to produce a wide range of complex hazardous gases, especially at high load. Moreover, diesel exhaust also contains a variety of heavy metal gases including aerosols and soot, sulfates, metallic abrasion particles, silicates and ash particulates. The main purpose of the study was to characterise the effects of diesel, biodiesel blends B5M10 and B10M10 and emulsion fuels B5M10E3 and B10M10E3 as fuels for the impact on gas emission. Engine tests have been performed to obtain results of fuel properties, engine performance and gas emission with various cycles. The B5M10E3 produces lower NO_x emission results than B10M10E3 as biodiesel fuel increases the combustion temperature. In conclusion, biodiesel blends can actually reduce gas emissions compared to diesel but increase NO_x emissions. Therefore, emulsion fuels B5M10E3 and B10M10E3 can be the best alternative fuel for the future.